Placental Malaria is associated with reduced early life weight development of affected children independent of low birth weight - Palmero Melba S; Waight Pauline; Crozier Sarah; Miles David JC; Walther Brigitte; Ojuola Olubukola; Touray Ebrima; Sande Marianne; Whittle Hilton; Rowland-Jones Sarah; Flanagan Katie L (Malaria Journal, 2010)
Abstract Background Infection with Plasmodium falciparum during pregnancy contributes substantially to the disease burden in both mothers and offspring. Placental malaria may lead to intrauterine growth restriction or preterm delivery resulting in low birth weight (LBW), which, in general, is associated with increased infant morbidity and mortality. However, little is known about the possible direct impact of the specific disease processes occurring in PM on longer term outcomes such as subsequent retarded growth development independent of LBW. Methods In an existing West-African cohort, 783 healthy infants with a birth weight of at least 2,000 g were followed up during their first year of life. The aim of the study was to investigate if Plasmodium falciparum infection of the placenta, assessed by placental histology, has an impact on several anthropometric parameters, measured at birth and after three, six and 12 months using generalized estimating equations models adjusting for moderate low birth weight. Results Independent of LBW, first to third born infants who were exposed to either past, chronic or acute placental malaria during pregnancy had significantly lower weight-for-age (-0.43, 95% CI: -0.80;-0.07), weight-for-length (-0.47, 95% CI: -0.84; -0.10) and BMI-for-age z-scores (-0.57, 95% CI: -0.84; -0.10) compared to infants born to mothers who were not diagnosed with placental malaria (p = 0.019, 0.013, and 0.012, respectively). Interestingly, the longitudinal data on histology-based diagnosis of PM also document a sharp decline of PM prevalence in the Sukuta cohort from 16.5% in 2002 to 5.4% in 2004. Conclusions It was demonstrated that PM has a negative impact on the infant's subsequent weight development that is independent of LBW, suggesting that the longer term effects of PM have been underestimated, even in areas where malaria transmission is declining.